Efecto de las ondas de choque en la fascitis plantar. Riobamba, 2019 - Johanna Elizabeth, Caiza Crespo (2019)
The research work was aimed at the effect of shock waves on plantar fasciitis as an analgesic treatment in acute, subacute and chronic pain in a population between 18 and 75 years of age of the Basic Military Hospital No. 11 B.C.B. Galapagos, located in the city of Riobamba, province of Chimborazo. The research applied a field design, which is responsible for collecting data directly from the reality where the events occur, it included the observation technique carried out by the means of initial, intermediate, final record and analysis of the data taken, the interview, clinical history and the analog pain assessment scale (APAS) were used as corresponding instruments. The statistical software SPSS was used for the cause and exegesis of the information. The results obtained in the investigation showed that there was a greater incidence of plantar fasciitis in the male sex with (83.3%) of the population studied in patients with plantar fasciitis of the Basic Military Hospital No. 11 B.C.B Galapagos. The time of application of the treatment of extracorporeal shock waves (TESW), was about six weeks (2 sessions per week), reaching to reduce pain eloquently, goes from moderate-intense to moderate pain in 47%, of moderate at 50% level and 3% absence of pain; He appreciated that the effect of shock waves as an analgesic treatment gave favorable results for plantar fasciitis, improving the quality of life to perform normal daily life activities (DLA).